The Importance of the Role of Women Ulama as the Effort to Actualate the Message of Islam to the Value of Equality - Dewi Avivah (Universitas Islam Negeri Walisongo Semarang, 2021)
Islam is a gender-just religion so that in the dissemination of its values, gender-fair spaces and opportunities are also needed. The purpose of this study is to provide understanding and understanding to the reader that in realizing a gender-just environment, religion is an important slice that needs to be considered. Islam has agreed to create a gender-just order, and it has been stated in the verses of the Koran. This research method uses qualitative research, sourced from reading material and supported by implementation pictures as supporting data. The results showed that the presence of female clerics was very important. Islam has conveyed Islamic teachings by realizing gender justice so that resistance to patriarchal culture in Indonesia can be carried out with the presence of female ulama to understand that women also have human potential so that they can be said to be worthy as scholars. The limitation of this research is that the author is a little complicated in compiling the historical sequence of the presence of women ulama until their existence today. The lack of data sources that the author must obtain is still rare especially in research about Women Ulama as part of the struggle for gender equality.